Development of person‐centred quality indicators for aged care assessment services in Australia: A mixed methods study - Sandra Smith; Catherine Travers; Natasha Roberts; Melinda Martin‐Khan (Wiley, 2024)
Abstract Introduction This study developed a proposed set of person‐centred quality indicators (PC‐QIs) for services that assess older adults' care and support needs to determine their eligibility to receive government‐funded aged care services in Australia. Individual proposed PC‐QIs amenability for change within current organizational structures were explored. Barriers and opportunities to adapt service elements of the aged care assessment service to better align with the intent of the proposed PC‐QIs were identified. Methods A mixed methods study was conducted over five phases. A scoping review identified domains of quality for aged care services as perceived by older adults. Service elements of an aged care assessment service were mapped alongside quality domains informing key attributes of each quality domain. Self‐determination theory was used to formulate each proposed PC‐QI to align with key attributes and quality domains. Consultation with a consumer group enabled revision of the proposed PC‐QIs. A focus group with clinicians evaluated the amenability of each proposed PC‐QI for change and identified barriers and opportunities to better align service elements with older adults' perceptions of quality. Results were informed by qualitative and quantitative data from a structured focus group. Focus group discussions were audio recorded and subsequently transcribed verbatim. Qualitative data were analyzed using a deductive thematic approach by two independent researchers. Results Twenty‐four proposed PC‐QIs were developed. Refinement to descriptors of the proposed PC‐QIs were made by the consumer group (n = 18) and all were affirmed as being amenable to change by aged care assessors. Barriers in meeting the intent of the proposed PC‐QIs were identified across five domains including: health care staff knowledge (18.7%; n = 3); clear communication (31%; n = 5); person‐centred approach (18.7%; n = 3); respect for client (18.7%; n = 3); and collaborative partnership with client (12%; n = 2). Participants made 21 recommendations. Of the five service elements in delivering an aged care assessment service, barriers in meeting the intent of the proposed PC‐QIs were identified at the intake and booking of an assessment and during the assessment. Conclusions Recommendations identified provide assessment services guidance on ways to adapt service elements to better align with older adults' perceptions of quality. Patient and Public Contribution Patients and carers were involved as collaborators in this project at the protocol stage which included participating in discussions regarding the refining and modification of the protocol, refinement of the proposed PC‐QIs, data collection forms and supplementary information for participants.